2013
DOI: 10.1188/13.cjon.e52-e57
|View full text |Cite
|
Sign up to set email alerts
|

A Nurse Practitioner-Led Urgent Care Center: Meeting the Needs of the Patient With Cancer

Abstract: Providing comprehensive care for patients with cancer is complex with regard to severe treatment-related side effects. Hundreds of thousands of patients with cancer visit the emergency department (ED) each year, and more than half report multiple visits. In the United States, few of the National Cancer Institute-designated cancer centers have an ED specifically for patients with cancer. EDs often are an overcrowded and expensive way in which to care for the urgent needs of patients with cancer. In addition, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
20

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 25 publications
(23 reference statements)
1
36
0
20
Order By: Relevance
“…Several studies have explored the role of APRN-led supportive care clinics embedded in oncology practices and have demonstrated beneft in providing urgent access for symptom management and in some cases, reducing rates of hospitalization. [9][10][11] Our study fndings are supported by other fndings showing that the highest level of ED and supportive clinic use is in advanced cancer patients, most commonly in those with lung or breast cancer who are receiving cytotoxic che-motherapy. 5,9,[12][13][14][15] In addition, the uncontrolled symptoms of shortness of breath, pain, weakness, fever, nausea, vomiting, and diarrhea which commonly led to ED visits in our patient population were consistently the top sources of distress in other published studies 5,9,[12][13][14] Of those, pain, nausea, and vomiting have been identifed in 2 studies as potentially avoidable reasons for hospitalization.…”
Section: Discussionsupporting
confidence: 80%
“…Several studies have explored the role of APRN-led supportive care clinics embedded in oncology practices and have demonstrated beneft in providing urgent access for symptom management and in some cases, reducing rates of hospitalization. [9][10][11] Our study fndings are supported by other fndings showing that the highest level of ED and supportive clinic use is in advanced cancer patients, most commonly in those with lung or breast cancer who are receiving cytotoxic che-motherapy. 5,9,[12][13][14][15] In addition, the uncontrolled symptoms of shortness of breath, pain, weakness, fever, nausea, vomiting, and diarrhea which commonly led to ED visits in our patient population were consistently the top sources of distress in other published studies 5,9,[12][13][14] Of those, pain, nausea, and vomiting have been identifed in 2 studies as potentially avoidable reasons for hospitalization.…”
Section: Discussionsupporting
confidence: 80%
“…In our study, patients often waited until their symptoms were so severe that some patients considered stopping treatment in part because they were not entirely sure when to call their clinicians. The symptoms identified by patients as problematic included pain and gastrointestinal problems (ie, nausea/vomiting), which are among the most common symptoms and are associated with urgent care visits . This finding suggests that providing information to patients and caregivers about self‐management strategies and when to call clinicians may be beneficial.…”
Section: Discussionmentioning
confidence: 96%
“…The symptoms identified by patients as problematic included pain and gastrointestinal problems (ie, nausea/vomiting), which are among the most common symptoms and are associated with urgent care visits. 22 This finding suggests that providing information to patients and caregivers about self-management strategies and when to call clinicians may be beneficial. Similar to our findings, Lubberding and colleagues 23 also found that cancer survivors reported being ill-prepared to manage symptoms during the posttreatment period and that receipt of personalized advice and tailored supportive care were identified as desirable interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is clear evidence that NPs are providing care in oncology 15, 16, 17, a thorough review of the literature describing that care has not been conducted. Initially, a systematic review of the literature was planned.…”
Section: Scoping Review Methodologymentioning
confidence: 99%